Gonadal Histopathological Disorders in Mytilus galloprovincialis Male Exposed to Tars Used in Mussel Farms - Alonso, Ana; Suárez, Pilar; Ruiz, Yolanda; Dobal, Vladimir; San Juan, Fuencisla (Frontiers in Marine Science, 2019)
Polycyclic aromatic hydrocarbons (PAHs) and trace metals are pollutants widely distributed in the marine environment with toxic effects on live organisms, but few laboratory studies have proved their causal relationship with histopathologic alterations from invertebrates. We analyse the histopathologic effects of a tar mixture used in mussel farms on the gonad of male mussels. Mussels were exposed to water-accommodated fractions from different sub-lethal concentrations of that tar mixture during different times. The accumulation of PAHs and metals in mussels was quantified in each one tar exposure condition, and a comparative histological and morphometric analysis of the male gonad was performed, as well as of the gametogenic disorders and the cellular pathologies induced. Spermatogenesis disruption and alterations of somatic and germinal cells were observed as a direct effect of treatment. The pathologies observed followed an increasing malignity sequence depending on dose and exposure time: spawning induction; arrest of spermatogenesis and spermiogenesis; suppression of immune response; dysplasia of Sertoli and connective cells and finally, severe disorders of germinal cells. We demonstrate for the first time that tar used in waterproofing of floating rafts from the mussel farms causes severe effects on male mussel gonad, constituting a direct risk to the health of these organisms, affecting gametogenesis, quality of gametes and, ultimately, the sustainability of this resource and their quality for human consumption. Moreover, we propose the pathologies described in mussel as biomarkers of marine pollution and the mussel gonad as study model of testicular toxicity mechanisms in male reproduction.